BiblioMetric Analysis in the DevelopMent of Research on Covid-19 Policy in Indonesia in 2020-2022 - ULFAH OKTARIDA SIHALOHO; HERU NURASA; RAMADHAN PANCASILAWAN (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2023)
This study tries to analyze the bibliographical character and con-tent of covid policy articles published in Scopus indexed journals and written from 2020- 2022. We retrieved data from Scopus Database on July 14, 2022 at 13:50. We use “Covid-19 Policy Indonesia” as a keyword with several categories, namely title, abstract and keywords, filtered by subject area (social science; business, management, and accounting). We only include articles written in English. We processed and analyzed the data using VOS viewer software and co-occurrence visualization of keywords and bibliographies of sources and countries combined. Results: Based on the study protocol, we found 211 documents with the key- word covid policy during 2020-2022. Of the 2 subject areas, social science is the most productive field in publishing covid policy articles. Covid-19 Policy Indonesia has been published in 136 journals. In total, there are 30 countries collaborating to make research related to Covid-19 policies in Indonesia. The Journal of the Review of International Geographical education Online and the Bulletin of Indonesian Economic Studies are the journals that publish the most articles on this topic. Indonesia is the country that publishes the most with 183 articles. From a global perspective, research on covid policies in the 2020 - 2022 range has increased. There are 7 clusters. Indonesia has quite a lot of research related to the Covid-19 Policy in Indonesia, but not many studies have discussed Public Administration. Research themes for covid-19 policies in Indonesia related to Public Administration, Policy Innovation and Collaborative Governance will be interesting to be researched in the future. There is also an opportunity to conduct research on Covid-19 Policy in the context of social science related to public administration.